Reengaging Customers through Influencer Partnerships Strategies and Outcomes for Big Brands - Damayanti, Dita (Celebes Scholar pg, 2023)
his study investigates the effectiveness of various influencer marketing strategies in reengaging customers for large brands. Utilizing a quantitative approach, the research involved a comprehensive online survey distributed through email and social media, gathering data from respondents. The study examined four key strategies: sponsored posts, product reviews, giveaways/contests, and collaborative content. Statistical analyses, including regression, ANOVA, and correlation, were employed to assess the impact of these strategies on customer engagement and purchase intentions. The results indicate that giveaways and contests are the most effective in enhancing engagement and purchase intentions, with significant correlations found between influencer credibility and engagement metrics. These findings address existing gaps in the literature by providing empirical evidence on the relative effectiveness of different strategies and the importance of influencer attributes. The study offers practical insights for brands seeking to optimize their influencer marketing efforts and suggests avenues for future research.